End‐user satisfaction with Hurricane Dorian information in Atlantic Canada. (10th June 2022) - Silver, Amber; Finnis, Joel; Behlendorf, Brandon; Reid‐Musson, Emily
Abstract: Both Environment and Climate Change Canada (ECCC) and the National Oceanic and Atmospheric Administration have focused significant time and resources towards improving their forecast products. However, weather prediction remains an imperfect science, and as such, it is not unusual for meteorologists to prioritize accuracy over consistency or vice versa. There is considerable debate within the literature about whether (and how) inaccuracies and/or inconsistencies in forecasting will affect end‐user trust in future warnings. Hurricane Dorian presented the opportunity to explore the intersection between these concepts as its messaging was at times both inaccurate (e.g., then‐President Donald J. Trump indicated the storm would directly affect the state of Alabama) and inconsistent (i.e., both the storm's forecasted intensity and track changed over time). Two research projects were undertaken in Atlantic Canada: the first utilized semi‐structured interviews to examine the ways that ECCC meteorologists ( n = 6) perceived the needs of their end‐users during the storm. There was considerable concern that changes in the storm's forecasted track and intensity would negatively influence public response. The second project utilized a large sample questionnaire ( n = 1218) to examine ways that end‐users searched for, shared, and responded to storm‐related information. Despite changes in the storm's track and intensity as it approached Atlantic Canada, as well as the international news coverage of Sharpiegate, respondents overwhelmingly agreed that the storm was well forecasted and its impacts were well predicted. The implications for this (seemingly) contradictory response are explored in the context of probabilistic forecast potential. Abstract : Responses to five‐point Likert scale questions on perceptions of general storm‐related information.